An Unusual Presentation of Pancreatic Neuroendocrine Carcinoma in a Young Woman: A Case Report - Iman Hakim Wicaksana; Suryo Wahyu Raharjo (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Pancreatic neuroendocrine tumors (PNETs) are rare neoplasms arising from the endocrine cells of the pancreas. They are typically diagnosed in older adults, with a peak incidence between 70 and 74 years. PNETs in young adults are uncommon and often present with non-specific symptoms, leading to delays in diagnosis and treatment. Case presentation: We report the case of a 22-year-old woman who presented with a large, non-functional PNET located in the tail of the pancreas. The patient initially complained of vague abdominal discomfort, nausea, and vomiting. Imaging studies revealed a large, heterogeneous mass in the left upper quadrant. The patient underwent a distal pancreatectomy, and histopathological examination confirmed the diagnosis of a poorly differentiated pancreatic neuroendocrine carcinoma. Conclusion: This case highlights the challenges in diagnosing PNETs in young adults. Clinicians should maintain a high index of suspicion for PNETs in young patients presenting with abdominal symptoms, even in the absence of classic hormonal syndromes. Early diagnosis and surgical intervention are crucial for improving outcomes in these patients.